kajian teoretis maslahah mursalah pada inovasi keuangan islam digital - Maula, Faruq Habibil (Maliki Interdisciplinary Journal, 2025)
The swift evolution of digital technologies has led to the emergence of diverse innovations within the realm of Islamic finance, including Sharia-compliant fintech platforms, halal electronic wallets, and smart contracts utilizing blockchain infrastructure. These advancements necessitate a methodological renewal in Islamic legal thought to effectively respond to contemporary demands while upholding Sharia principles. This research explores the conceptual significance of maslahah mursalah in the context of digital Islamic financial innovation, employing both normative and analytical approaches. The study’s results indicate that maslahah mursalah functions as a dynamic framework for ijtihad, enabling the incorporation of socio-technological transformations while safeguarding the objectives of Islamic law (maqāṣid al-syarī‘ah), particularly the protection of wealth (ḥifẓ al-māl) and religion (ḥifẓ al-dīn). Consequently, digital financial innovations may be regarded as means of public welfare, provided they remain consistent with scriptural sources and Sharia norms.